The widow's house - Abraham, Daniel (Abraham, Daniel. Dagger and the coin, 2014)
"Lord Regent Geder Palliako's war has led his nation and the priests of the spider goddess to victory after victory. No power has withstood him, except for the heart of the one woman he desires. As the violence builds and the cracks in his rule begin to show, he will risk everything to gain her love or else her destruction. Clara Kalliam, the loyal traitor, is torn between the woman she once was and the woman she has become. With her sons on all sides of the conflict, her house cannot stand, but there is a power in choosing when and how to fall. And in Porte Oliva, banker Cithrin bel Sarcour and Captain Marcus Wester learn the terrible truth that links this war to the fall of the dragons millennia before, and that to save the world, Cithrin must conquer it"--